1998
DOI: 10.1161/01.cir.97.13.1239
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stroke Complicating Carotid Artery Stenting

Abstract: Background-The evolving technique of carotid stenting is being evaluated as an alternative to endarterectomy.Identification of the factors that predispose a patient to neurological complications would facilitate further refinement of the technique and optimize patient selection. Methods and Results-We analyzed the impact of various clinical, morphological, and procedural determinants on the development of procedural strokes in 231 patients who underwent elective (primary) stenting of 271 extracranial carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
161
3
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(175 citation statements)
references
References 25 publications
(13 reference statements)
6
161
3
5
Order By: Relevance
“…9,17,26,27 The reported rate of severe bilateral carotid stenosis and/or occlusion varies widely (3.2%-39%) 8,9,17,28 and was encountered in 14.6% of the patients at high surgical risk in our prospective CAS data base. Although bilateral carotid stenosis has been shown to potentially increase the risk for complications during CEA or CAS and has been included as 1 of the high risks for CEA, our data revealed that there was no significant difference in outcome at 30 days or at 6 months between the bilateral and unilateral stent-placement patient groups.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…9,17,26,27 The reported rate of severe bilateral carotid stenosis and/or occlusion varies widely (3.2%-39%) 8,9,17,28 and was encountered in 14.6% of the patients at high surgical risk in our prospective CAS data base. Although bilateral carotid stenosis has been shown to potentially increase the risk for complications during CEA or CAS and has been included as 1 of the high risks for CEA, our data revealed that there was no significant difference in outcome at 30 days or at 6 months between the bilateral and unilateral stent-placement patient groups.…”
Section: Discussionmentioning
confidence: 93%
“…4,5 Since Mathur et al 6 first reported the feasibility of staged CAS for bilateral carotid stenosis, some small series have been published in an attempt to promote staged or simultaneous revascularization. [7][8][9][10][11][12][13][14][15][16] However, the results have been equivocal, and there is an obvious need for larger trials to firmly establish the superiority of the simultaneous or the staged approach. Nonetheless, patients with bilateral carotid artery disease have been excluded from most prospective trials due to concerns regarding possible complications and/or poor outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All patients underwent neurological examination the day after the procedure. Post-procedural complications, according to Mathur et al [17] classification, were defined as follows:…”
Section: Definitions and Follow-upmentioning
confidence: 99%
“…The clinical outcome measures were minor or major stroke or death within 30 days and were defined as follows 17 :…”
Section: Definitions Of Clinical Outcome Measuresmentioning
confidence: 99%